WHOSE PAST COUNTS? SUBALTERN KNOWLEDGE AND THE POLITICS OF WRITING HISTORY - Pratheesh Padath; Mary Reema (KRONIK : Journal of History Education and Historiography, 2026)
This article critically examines the epistemic assumptions that govern modern historiography by interrogating how historical authority is constructed and whose pasts are recognised as legitimate historical knowledge. It argues that dominant traditions of history writing have systematically privileged archival, state-centred, and elite sources, thereby marginalising subaltern forms of knowledge embedded in oral traditions, embodied practices, labour processes, and community memory. Rather than approaching subaltern knowledge as a normative or ethical counterpoint to elite narratives, the article conceptualises it as an epistemic category that unsettles the hierarchy of historical evidence itself. Through a critical engagement with historiographical debates in subaltern studies, postcolonial theory, and archival criticism, the study demonstrates how historical silences are produced not by the absence of past experiences, but by regimes of documentation and interpretive authority. The article advances a methodological framework that advocates epistemic pluralism while retaining the principles of verification, triangulation, reflexivity, and ethical responsibility essential to historical inquiry. It contends that integrating subaltern knowledge into historiography requires neither the rejection of archives nor the romanticisation of marginal voices, but a reconfiguration of evidentiary evaluation and historical reasoning. The final section addresses the implications of this reorientation for history education, arguing that pedagogical engagement with multiple forms of historical evidence can cultivate critical historical thinking, deepen students’ understanding of knowledge construction, and challenge the reproduction of singular and exclusionary narratives of the past. By foregrounding the politics of historical knowledge production, the article contributes to broader debates on historiography and history education concerning whose past counts, and on what epistemic grounds.